1995
DOI: 10.1103/physreve.51.4690
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion model with oil-water anisotropy

Abstract: We consider a spin model for applications to oil-water -amphiphilic-surfactant mixtures near the region where those phases coexist. We analyze this model assuming that oil and water molecules cannot be treated symmetrically, given that they do exhibit different chemical potentials. Using a mean-field approximation, we find that the modulated phase assumes two possible arrangements, such as sheets (lamellar phase) or rods (hexagonal phase). Due to fluctuations, the lamellar phase is present when the difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Recent experiments by Bates et al [10] found experimental evidence for a bicontinuous polymeric microemulsion in an asymmetric homopolymer copolymer mixture in a region where the self-consistent field theory predicts an isotropic Lifshitz point. In fact, the experimental phase diagram of the copolymer homopolymer mixture closely resembles the phase diagram of small molecule mixtures of oil, water and amphiphiles [127].…”
Section: Copolymers At Interfacesmentioning
confidence: 64%
“…Recent experiments by Bates et al [10] found experimental evidence for a bicontinuous polymeric microemulsion in an asymmetric homopolymer copolymer mixture in a region where the self-consistent field theory predicts an isotropic Lifshitz point. In fact, the experimental phase diagram of the copolymer homopolymer mixture closely resembles the phase diagram of small molecule mixtures of oil, water and amphiphiles [127].…”
Section: Copolymers At Interfacesmentioning
confidence: 64%